An Unusual Cause of Abdominal Pain: Three Lead Pellets within the Appendix Vermiformis. (28th May 2015) - Ozkan, Orhan Veli; Muderris, Vecdi; Altintoprak, Fatih; Yagmurkaya, Orhan; Yalkin, Omer; Celebi, Fehmi
Abstract : Most ingested foreign bodies usually pass out in the feces uneventfully. Complications such as intestinal perforation and bleeding usually occur with sharp, thin, stiff, long, and pointed objects. This case describes the management of three lead pellets within the appendix vermiformis. A 45-year-old male visited our clinic complaining of a 4-month history of abdominal pain. The patient inquiry revealed that he had eaten hunted rabbit meat on numerous occasions and had unintentionally ingested three lead pellets. Plain abdominal films and a barium enema showed foreign bodies in the right lower abdominal quadrant. Since the lead pellets were thought to have migrated extraluminally, they were removed through laparotomy under fluoroscopic guidance. An appendectomy was performed. Pathologically, three lead pellets were embedded in the appendix, which showed signs of intramucosal inflammation. Foreign bodies causing appendicitis are rare. However, if stiff or pointed objects enter the appendicular lumen, there is a high risk of appendicitis, perforation, or abdominal pain. An appendectomy was required to remove the ingested lead pellets in the appendix.